Reimagining Christian Education: Cultivating Transformative Approaches - Luetz, Johannes M.; Dowden, Tony; Norsworthy, Beverley (SpringerLink Bücher, 2018)
This book is an arresting interdisciplinary publication on Christian education, comprising works by leading scholars, professionals and practitioners from around the globe. It focuses on the integrated approaches to Christian education that are both theoretically sound and practically beneficial, and identifies innovative pedagogical methods and tools that have been field-tested and practice-approved. It discusses topics such as exploring programmes and courses through different lenses; learning challenges and opportunities within organisational management; theology of business; Christian models of teaching in different contexts; job preparedness; developing different interpretive or meaning-making frameworks for working with social justice, people with disability, non-profit community organisations and in developing country contexts. It offers graduate students, teachers, school administrators, organisational leaders, theologians, researchers and education practitioners a fresh and inspiring reimagining of Christian education perspectives and practices and the ramifications of their application to life-long learning